The E and B EXperiment: implementation and analysis of the 2009 engineering flight. - Milligan, Michael Bryce (2011)
University of Minnesota Ph.D. dissertation. June 2011. Major: Astrophysics. Advisor: Shaul Hanany. 1 computer file (PDF); x, 132 pages, appendices A-D. The E and B EXperiment (EBEX) is a balloon-borne telescope designed to map the polarization of the cosmic microwave background (CMB) and emission from galactic dust at millimeter wavelengths from 150 to 410 GHz. The primary science objectives of EBEX are to: detect or constrain the primordial B-mode polarization of the CMB predicted by in ationary cosmology; measure the CMB B-mode signal induced by gravitational lensing; and characterize the polarized thermal emission from interstellar dust. EBEX will observe a 420 square degree patch of the sky at high galactic latitude with a telescope and camera that provide an 80 beam at three observing bands (150, 250, and 410 GHz) and a 6:2#14; diffraction limited field of view to two large-format bolometer array focal planes. Polarimetry is achieved via a continuously rotating half-wave plate (HWP), and the optical system is designed from the ground up for control of sidelobe response and polarization systematic errors. EBEX is intended to execute y or more Antarctic long duration balloon campaigns. In June 2009 EBEX completed a North American engineering flight launched from NASA's Columbia Scientific Ballooning Facility (CSBF) in Ft. Sumner, NM and operated in the stratosphere above 30 km altitude for #24; 10 hours. During flight EBEX must be largely autonomous as it conducts pointed, scheduled observations; tunes and operates 1432 TES bolometers via 28 embedded Digital frequency-domain multiplexing (DfMux) computers; logs over 3 GiB/hour of science and housekeeping data to onboard redundant disk storage arrays; manages and dispatches jobs over a fault-tolerant onboard Ethernet network; and feeds a complex real-time data processing infrastructure on the ground via satellite and line-of-sight (LOS) downlinks. In this thesis we review the EBEX instrument, present the optical design and the computational architecture for in-flight control and data handling, and the quick-look software stack. Finally we describe the 2009 North American test flight and present analysis of data collected at the end of that flight that characterizes scan-synchronous signals and the expected response to emission from thermal dust in our galaxy.